Long-term safety and efficacy of erenumab in patients with chronic migraine: Results from a 52-week, open-label extension study. (May 2020) - Tepper, Stewart J; Ashina, Messoud; Reuter, Uwe; Brandes, Jan Lewis; Doležil, David; Silberstein, Stephen D; Winner, Paul; Zhang, Feng; Cheng, Sunfa; Mikol, Daniel D
Background: This study reports the long-term safety and efficacy of erenumab in chronic migraine patients. Methods: This was a 52-week open-label extension study of a 12-week double-blind treatment phase study. During the double-blind treatment phase, patients received placebo or once-monthly erenumab 70 mg or 140 mg. During the open-label treatment phase, the initial monthly dose was erenumab 70 mg. Following protocol amendment, patients continued to receive erenumab 70 mg if they had already completed their Week 28 visit, otherwise, patients switched from 70 mg to 140 mg; if enrolled after the amendment, patients received 140 mg monthly throughout. Results: In all, 451/609 (74.1%) enrolled patients completed the study. The exposure-adjusted patient incidence rate for any adverse event was 126.3/100 patient-years for the overall erenumab group. Overall, the adverse event profile was similar to that observed in the double-blind treatment phase. Adverse event incidence rates did not increase with long-term erenumab treatment compared with the double-blind treatment phase, and no new serious or treatment-emergent events were seen. Efficacy was sustained throughout the 52 weeks. Clinically significant reductions from double-blind treatment phase baseline (about half) were observed for monthly migraine days and migraine-specific medication days. Achievement of ≥50%, ≥75% and 100% reductions from the double-blind treatment phase baseline in monthly migraine days at Week 52 were reported by 59.0%, 33.2% and 8.9% of patients, respectively, for the combined dose group. A numerically greater benefit was observed with 140 mg compared with 70 mg at Weeks 40 and 52. Conclusions: Sustained efficacy of long-term erenumab treatment in patients with chronic migraine is demonstrated, with safety results consistent with the known safety profile of erenumab and adverse event rates comparable to placebo adverse event rates in the double-blind treatment phase. Trial registration: This study is registered at ClinicalTrials.gov (NCT02174861)